Analisis Berkomunikasi dalam Keterampilan Proses Sains Siswa melalui Pembelajaran Daring pada Mata Pelajaran IPA Kelas VI di SDN 2 Negerikaton Pesawaran Lampung - Putri Wahyuningsih; Siti Fatonah (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2021)
Communication is the basic principle of a learning process. A person's communication skills are trained by communicating what is on his mind both orally and in writing. The stage of communicating in science process skills is the last stage in which students must be able to convey the results of the learning process and to assess the extent to which students understand the results of the learning that has been obtained. The purpose of this study is to examine deeper science process skills at the stage of communicating and knowing and identifying the intensity and quality of teacher and student communication during online learning. The research approach used is descriptive analytical using a qualitative approach. Data collection techniques used include observation, interviews, and documentation. The subjects of this study were the principal, teachers, students and parents. The results of this study are as follows: First, science process skills at the stage of communicating fifth grade students in science subjects in the form of reporting data on the results of their assignments both orally and in writing are in good criteria. It is proven that students only understand the concept of tables and are less able to distinguish between tables and graphs. Second, communication is important in teaching and learning activities. Communication is a prerequisite for interaction between teachers and students in teaching and learning activities, both offline learning and online learning. The intensity of communication during online learning is only once a week through the whatsapp group. The form of verbal communication in the form of writing, namely the activities of the teacher providing material and students collecting assignments through chatting on the WhatsApp group.